The effects of aerobic exercise in patients with cancer-related fatigue: A systematic review and meta-analysis - Tong Wang; Jiaxin Deng; Weicheng Li; Qiubo Zhang; Haoming Yan; Yongfeng Liu (PLoS ONE, 2025)
Background Cancer-related fatigue (CRF) is characterized by an unusual and persistent sensation of tiredness that can occur during or after treatment, potentially impacting both physical and mental capability, and which does not ameliorate with rest. Aerobic exercise (AE) has been identified as a potent modality to mitigate the severity of CRF in such patients. Objective This study aims to investigate the efficacy of AE in alleviating CRF among patients. Methods A comprehensive literature search was implemented on PubMed, Web of Science, EBSCO, Cochrane, and Embase until June 2024. Studies were selected based on the following PICOS criteria: Participants (P): cancer patients undergoing treatment or in recovery; Intervention (I): aerobic exercise, including activities such as walking, running, yoga, or tai chi; AE interventions conducted during both treatment and recovery were included. Comparison (C): usual care, no-treatment/wait-list, or attention/activity placebo controls; Outcome (O): cancer-related fatigue (CRF) measured by validated scales; Study design (S): randomized controlled trials (RCTs). The meta-analysis was performed using Review Manager 5.3. Results The results indicate that AE exerts a significant impact on CRF, but the heterogeneity is high (SMD = −0.76, 95% CI: −1.30 to −0.22, P < 0.05, I² = 94%). Subgroup analysis revealed that AE interventions lasting at least 12 weeks (SMD = −1.12, 95% CI = −2.02 ~ −0.22, P < 0.05, I² = 96%), 3 times or less per week (SMD = −1.00, 95% CI = −1.83 ~ −0.16, P < 0.05, I2 = 96%), with each session exceeding 60 minutes (SMD = −1.48, 95% CI = −2.32 ~ −0.64, P < 0.01, I2 = 96%), compared to the control group, significantly improve CRF in patients. Conclusion The research findings confirm the effectiveness of AE in alleviating CRF. Subgroup analysis further elucidated that AE interventions lasting at least 12 weeks, 3 times or less per week, with 60 minutes or more per session, significantly alleviated CRF among patients. However, given the limited number of included studies, caution is warranted in interpreting these subgroup analysis outcomes. The protocol for this review was duly registered on PROSPERO under the registration number CRD42024559098.